Implementasi Dan Fungsi Algoritma Pemrograman pada Kehidupan Sehari-hari - Sarah Rizki Pebriani; Yahfizham Yahfizham (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
An algorithm is an effective method or steps arranged in writing and sequentially containing a collection of commands to solve a problem. Every problem must be resolved logistically, systematically and organized. Programming is a process that allows computers to solve or solve problems in the form of solving steps, as done in programming code languages, so that computers can actually solve problems. A programming algorithm is a systematic collection of steps aimed at solving any computer programming problem. Based on the writing format, the application of the programming algorithm is descriptive, pseudocode, and flowchart. And the basic structure of a programming algorithm can be used in three forms: sequence, selection, and repetition. Algorithm writing is not governed by any particular rules; however, each step of the algorithm must have a clear goal. The purpose of writing this article is to study the functions and various implementations of programming algorithms and their applications in everyday life. To achieve this goal, this article was written using the literature study method, which means reading systematically and in an organized manner books, journals and other sources related to programming algorithms. Programming algorithms have many very important functions. Solving a problem is the main function of a programming algorithm. Algorithms function to simplify programs, make it easier to find errors, and minimize repetitive program writing. Programming algorithms also have implementations and functions for us in everyday life. Examples of algorithms in our daily activities, such as installing applications, sending emails, receiving payments at ATMs, making fried noodles, making cakes, making coffee, riding motorbikes, cooking rice, etc.